Research Topics on Railway Vehicle Dynamics - Takahiro Tomioka (EPI International Journal of Engineering, 2018)
Engineering research subjects relating railway vehicle dynamics are described as a literature survey in this paper. Research works concerning to the motion of wheelset; pantograph-catenary interaction; aerodynamic relating problems on the vehicle; and application of control techniques are introduced firstly as the most distinctive subjects of railway vehicle dynamics. The topics on safety assessment and ride comfort evaluation are also dealt with since those are important research area in railway dynamics as public transportation system. The subject concerning to carbody elastic vibration, which is important relating to ride comfort, is also described. The effect of passengers on the elastic vibration of carbody has been introduced as the interesting (and something surprising) topic. The focuses in the literature survey are particularly on the research works from Japan, in this paper.